NANOPARTICLE FABRICATION OF COxNi1-xFe2O4 (x=0,0.25,0.5,0.75,1.0) USING CO-PRECIPITATION METHODE AT LOW TEMPERATURE - Yakob, Muhammad; Putra, Rachmad Almi (Jurnal Neutrino, 2019)
Nanoparticle CoxNi1-xFe2O4 has been successfully synthesized using co-precipitation method at low temperature 120oC by variation of concentration value (x=0; 0.25; 0.5; 0.75; 1.0). Crystal structure and size of crystallite increase with increasing cobalt concentration. There is a difference of lattice between theoretical and experimental. Increase the cobalt concentration in CoxNi1-xFe2O4 nanoparticle affected to the bond length between cation-anion on tetrahedral site and octahedral site. Because of the distortion, the crystallite where imperfectly formed and crystal defect occurred. It is indicated by the microstrain value that describes the magnitude of the strain in crystal.